Does External Accountability Affect Student Outcomes? A Cross-State Analysis - Carnoy, Martin; Loeb, Susanna (Educational Evaluation and Policy Analysis, 2002)
We developed a zero-to-five index of the strength of accountability in 50 states based on the use of high-stakes testing to sanction and reward schools, and analyzed whether that index is related to student gains on the NAEP mathematics test in 1996–2000. The study also relates the index to changes in student retention in the 9th grade and to changes in high school completion rates over the same period. The results show that students in high-accountability states averaged significantly greater gains on the NAEP 8th-grade math test than students in states with little or no state measures to improve student performance. Furthermore, students in high-accountability states do not have significantly higher retention or lower high school completion rates.